Analisis Strategi Segmentation, Targeting, Positioning Di PT Pubdok Creative Technologies Sumedang - Putri, Aanisa Syama Insani; Putri, Amalia Dwi; Dewi, Cici Komala; Komara, Achmad Ridwan; Hidayat, Hikmal Raihan (SINTESA, 2025)
This study aims to analyze the segmentation, targeting, and positioning strategies implemented by PT Pubdok Creative Technologies Sumedang, also known as Studio Foto Pubdok, a company engaged in photography services. The research method used is qualitative, with data collected through interviews, observation, and documentation. The number of informants in this study is 10, selected using purposive sampling. The data analysis techniques used in this study include data collection, data reduction, data display, and drawing/verification. Based on the data analysis results, the company implements a segmentation strategy using four bases: demographic, geographic, psychographic, and behavioral. The targeting strategies applied include differentiated segment, undifferentiated segment, and concentrated marketing. As for positioning, the strategies used are based on attributes, benefits, usage/application, user, competitor, product category, and price/quality.